2012
DOI: 10.1111/jcpe.12007
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive clinical effect of a water‐cooled Nd:YAGlaser in a periodontal maintenance care programme: a randomized controlled trial

Abstract: In residual pockets ≥5 mm, treated in a PMC, the adjunctive use of an Nd:YAG laser does not provide a clinically significant additional advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 23 publications
2
46
0
1
Order By: Relevance
“…Krohn‐Dale et al 34 compared the use of Er:YAG laser to conventional root planing every 3 months during 1 year and found no differences in clinical outcomes. Slot et al 35 compared the neodymium:yttrium‐aluminum‐garnet (1,064 nm wavelength) adjunctive with SRP to SRP alone in PMT patients with residual PD ≥5 mm. At 6 months after treatment, no differences between therapies were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Krohn‐Dale et al 34 compared the use of Er:YAG laser to conventional root planing every 3 months during 1 year and found no differences in clinical outcomes. Slot et al 35 compared the neodymium:yttrium‐aluminum‐garnet (1,064 nm wavelength) adjunctive with SRP to SRP alone in PMT patients with residual PD ≥5 mm. At 6 months after treatment, no differences between therapies were observed.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 During maintenance therapy, sites may [16][17][18] Diode laser-assisted periodontal therapy using photodynamic therapy was not superior to conventional mechanical debridement, 19 however photodynamic therapy was shown to be superior in eliminating pockets especially in single rooted teeth maintenance phase as seen by Campos et al 20 In our study, piezoelectric ultrasonic unit (EMS) was used to perform SRP. Chapper et al found that there was no significant difference found in treatment outcomes of ultrasonic scaling alone or ultrasonic scaling followed by hand scaling as the final step.…”
Section: Discussionmentioning
confidence: 88%
“…Most previous studies reported on the use of lasers in periodontal therapy have mainly investigated diode, Erbium: Yttrium Aluminium Garnet (Er:YAG) and Nd:YAG lasers 5,6,10,11,12,13) . However, the Er,Cr:YSGG laser has had few studies in the field of periodontology, and on occasion has been grouped together with the Er:YAG laser due to having similar wavelengths and both having hard and soft tissue targets.…”
Section: Discussionmentioning
confidence: 99%